An analogue of atrial natriuretic peptide (C-ANP4-23) modulates glucose metabolism in human differentiated adipocytes. (15th August 2016) - Ruiz-Ojeda, Francisco Javier; Aguilera, Concepción María; Rupérez, Azahara Iris; Gil, Ángel; Gomez-Llorente, Carolina
Abstract: The present study was undertaken to investigate the effects of C-atrial natriuretic peptide (C-ANP4-23 ) in human adipose-derived stem cells differentiated into adipocytes over 10 days (1 μM for 4 h). The intracellular cAMP, cGMP and protein kinase A levels were determined by ELISA and gene and protein expression were determined by qRT-PCR and Western blot, respectively, in the presence or absence of C-ANP4-23 . The levels of lipolysis and glucose uptake were also determined. C-ANP4-23 treatment significantly increased the intracellular cAMP levels and the gene expression of glucose transporter type 4 ( GLUT4 ) and protein kinase, AMP-activated, alpha 1 catalytic subunit (AMPK ). Western blot showed a significant increase in GLUT4 and phosphor-AMPKα levels. Importantly, the adenylate cyclase inhibitor SQ22536 abolished these effects. Additionally, C-ANP4-23 increased glucose uptake by 2-fold. Our results show that C-ANP4-23 enhances glucose metabolism and might contribute to the development of new peptide-based therapies for metabolic diseases. Highlights: The synthetic ligand C-ANP4-23 increases the intracellular cAMP levels in human differentiated adipocytes. C-ANP4-23 up-regulates the gene and protein expression of GLUT4 and enhances glucose uptake, through AMPK activation. C-ANP4-23 enhances glucose metabolism and might contribute to the development of new therapies for metabolic diseases.